Development of Testing Frame for Diagonal Shear Test of Composite Panels and Engineered Wood Products - Jauhar Fajrin (Jurnal Ilmu dan Teknologi Kayu Tropis, 2015)
This paper reports the development of a testing frame for diagonal in-plane shear test of composite panels and engineered wood products. The study was divided into two subsequent experimental works. The first experiment was conducted by assessing several frame configurations with small-scale frame test. The second experimental work was conducted by applying the selected frame obtained from the first stage experiment to assess the in-plane shear performance of medium density fibre (MDF) board. The result shows that the developed testing frame has been able to generate a pure shear mechanism which is extremely important in the investigation of in-plane shear behaviour of composite panels and engineered wood products. Other important findings are includes; 1) frame with pin at all four corners and the tested panel located in between the upper and bottom frame and connected with bolts is the best choice for inducing in-plane shear mechanism, 2) the developed frame that has all four corners pin-jointed using bolts to obtain free-movement to vertical and horizontal directions works better than those with only two pin-jointed corner at the top and bottom corners that formerly developed by other reseachers.